State Sphere Shift into Public Sphere: E-Musrenbang Surabaya City - Christijanto, Eddy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This research was conducted to find out how a space formed by the government (state sphere) has the potential to turn into a public sphere which is deliberative because of the involvement of information technology. This research was carried out on the use of information technology in the implementation of electronic development planning meetings (E-musrenbang) in the City of Surabaya, East Java, Indonesia. This research was conducted qualitatively using a critical approach. The data processed and analyzed were obtained from community leaders in four villages in Surabaya. As a result, this study shows that the internet has provided opportunities for people to make the state sphere as a public sphere where people can act further and more freely as citizens to voice their aspirations, opinions, and ideas. As such, indirectly the participation of the community to be involved in regional development can be pushed to a higher level.